1999
DOI: 10.1046/j.1440-1681.1999.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐derived Hyperpolarizing Factor(s): Species and Tissue Heterogeneity

Abstract: 1. Endothelium-derived relaxing factor is almost universally considered to be synonymous with nitric oxide (NO); however, it is now well established that at least two other chemically distinct species (prostacyclin (PGI2) and a hyperpolarizing factor) may also contribute to endothelium-dependent relaxation. 2. Only relatively few studies have provided definitive evidence that an endothelium-derived hyperpolarizing factor (EDHF), which is neither NO nor PGI2, exists as a chemical mediator. 3. There is a lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…As predicted, we found that the efferent arteriole response to ACh does not exhibit this EDHFlike component. A number of studies have demonstrated regional differences in regard to the role of EDHF (39). This study is the first to demonstrate that, within the renal microcirculation, EDHF contributes to the regulation of preglomerular tone but does not affect the postglomerular efferent arteriole.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As predicted, we found that the efferent arteriole response to ACh does not exhibit this EDHFlike component. A number of studies have demonstrated regional differences in regard to the role of EDHF (39). This study is the first to demonstrate that, within the renal microcirculation, EDHF contributes to the regulation of preglomerular tone but does not affect the postglomerular efferent arteriole.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, it has been suggested that in resistance vessels endothelium-dependent hyperpolarization may not involve a released factor but rather may be mediated via myoendothelial gap junctional communication (4,23,35). Differing regions of the circulation exhibit considerable heterogeneity in regard to the nature of EDHF, its contribution to endothelium-dependent vasodilation, and the underlying ionic mechanisms (28,39). Since its discovery, the role of NO in the regulation of renal hemodynamics has received considerable attention.…”
mentioning
confidence: 99%
“…Indeed, EDHF-like dilations could be demonstrated only in perfused vascular preparations in the present study. This may simply reflect the fact that EDHF responses observed in different vascular beds from the same species or between species are highly variable (18). Alternatively, fluid shear stress may facilitate agonist-induced EDHF production in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P-450 (CYP)-derived arachidonic acid metabolites are postulated to (12), and hydrogen peroxide has been reported as an EDHF in mouse (13) and human mesenteric arteries (14). Therefore, the identity of EDHF appears to differ among vascular beds and animal species (15)(16)(17). Recently, it has been postulated that the myoendothelial gap junction is important for spreading membrane hyperpolarization from endothelial cells to smooth muscle cells (18,19).…”
Section: Introductionmentioning
confidence: 99%